Pengaruh Promosi Online dan Brand Image terhadap Keputusan Pembelian pada Produk Clothing Whynostalgia di Bogor - Damayanti, Dessyana; Subagja, Febrian Al Rasyid; Haedar, Mohamad Diaz (Fakultas Ekonomi dan Bisnis, 2022)
Small and medium enterprises (MSMEs) are a significant part of the economy of a country or region (including Indonesia). The development of the MSME sector has an important meaning in encouraging economic growth and reducing the poverty rate of a country. This study aims to determine the effect of online promotion and brand image on purchasing decisions on UMKM Whynostalgia products in Bogor. The data collection method used was the distribution of written questionnaires and the distribution of online questionnaires using Google Forms and path analysis is the data analysis technique used. The results of the analysis show that online promotion and brand image have a partially and simultaneously significant positive effect on purchasing decisions for UMKM Whynostalgia products in Bogor.